AKTUALISASI AKHLAK MAHASISWA UPI BERLATARBELAKANG PESANTREN DAN SEKOLAH UMUM - Sapaat Abdul Salam, - (2019)
This research is motivated by the deterioration of student morals which is very worrying, an intellectual candidate who must be an agent of change must be tainted by behavior that does not reflect the nation's successor. The flow of moderation, westernization that is too far so that it can crash into the rules of religion and state, on the other hand Islamic-based educational institutions continue to develop. This study aims to analyze the differences in the actual quality of the morality of pesantren alumni with public school alumni on the UPI campus. The method used in this study is a descriptive method with a quantitative approach to the comparative design of two independent variables, with a survey research design in the form of a questionnaire / questionnaire. Data is taken by one-step group sampling technique (cluster sampling sampling), while the data processing technique uses descriptive data analysis and inferential data analysis with the help of Microsoft Excel and SPSS 25 software. Based on the moral dimensions used as research, namely: Moral to yourself Morals towards parents and family, and Morals with fellow human beings and the community, it is known that the actualization of the morality of pesantren alumni students results in high moral qualifications, whereas the actualization of the morals of public school alumni is in moderate moral qualifications, the results of the study after comparison of the three dimensions that, it is known that the actualization of the morality of pesantren alumni students with public school alumni using the Chi square formula obtained a value of 34,147. If seen in the chi square table of 5% significance level that is equal to 5.991, then the value of chi squared in this study is greater that is 34.147> 5.991. From these results it is known that there are significant differences in the actualization of the morality of pesantren alumni students with public school alumni students. Keyword : Actualization, Character, Comparation, Pesantren, Public School